MITOS DI MEDIA SOSIAL TERKAIT PILPRES 2019 - Misbah Priagung Nursalim (PIKTORIAL : Journal of Humanities, 2019)
ABSTRACT Political noise in Indonesia raises the number of practical political actors on social media. Actors are generally citizens of various backgrounds and ages. The form of noise is in the form of expressions related to the presidential election on his social media account. Massive expressions have the potential to become myths. This research is very important to analyze the form of myths on social media related to the 2019 presidential election and how the process of the myth occurred. This study used descriptive qualitative method. The method rests on Rolland Barthes's semiotic theory. In order for the methods and theories to be used to find results, the author uses referral techniques to collect research data. Research data is taken from expressions in the form of words or phrases on social media related to politics ahead of the 2019 presidential election. The author found several words that have the potential to become myths, but only a few have formed new myths in society such as cebong, kampret, communists and onta. Keywords: myths, presidential election, semiology